1988
DOI: 10.1073/pnas.85.20.7753
|View full text |Cite
|
Sign up to set email alerts
|

Toward a population genetic analysis of Salmonella: genetic diversity and relationships among strains of serotypes S. choleraesuis, S. derby, S. dublin, S. enteritidis, S. heidelberg, S. infantis, S. newport, and S. typhimurium.

Abstract: Variation in the chromosomal genomes of newport) in isolates of clones belonging to several evolutionary lineages, some of which are distantly related, suggests that the horizontal transfer and recombination of chromosomal genes mediating expression of cell-surface antigens has been a significant process in the evolution of the salmonellae. Two divergent clone clusters of S. derby differ in the relative frequency with which they cause disease in birds versus mammals, and two major lineages of S. newport differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(114 citation statements)
references
References 24 publications
4
109
1
Order By: Relevance
“…S . typhimurium was one of three serovars whose specific antigen profile was shown by multilocus enzyme electrophoresis (MLEE) to be confined to a single cluster of closely related electrophoretic types (ETs), which were considered equivalent to chromosomal genotypes (Beltran et al, 1988). The lines of descent identified as IS200 profile groups in this study presumably occur within that single MLEE cluster, since all share three ancestral insertion sites.…”
Section: Discussionmentioning
confidence: 99%
“…S . typhimurium was one of three serovars whose specific antigen profile was shown by multilocus enzyme electrophoresis (MLEE) to be confined to a single cluster of closely related electrophoretic types (ETs), which were considered equivalent to chromosomal genotypes (Beltran et al, 1988). The lines of descent identified as IS200 profile groups in this study presumably occur within that single MLEE cluster, since all share three ancestral insertion sites.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to the Kauffmann-W hite serological scheme of classification have been emphasized by the demonstration that strains of the same serovar may be distantly related in multilocus enzyme genotype and that the 0 antigen groups of subgenus I may similarly be polyphyletic (Beltran et al, 1988;Selander et al, 1990a, b). This work has also shown that the population structure of the salmonellae is basically clonal, with each serovar being represented by one or a few predominant clones of widespread if not global distribution (Beltran et al, 1988 ;Reeves et al, 1989 ;Selander et al, 1990a, 6). Comparative sequencing of the flagellin genes in strains of several serovars has implicated both intragenic and interstrain recombination as mechanisms generating new serovars (Frankel et al, 1989;Smith & Selander, 1990;Smith et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…S. bongori, formerly referred to as ssp. V, was assigned a separate species based initially on its different biotype and phylogenetic data acquired by multilocus enzyme electrophoresis (MLEE) (1,2).…”
mentioning
confidence: 99%